Efficacy and safety of Kunxian in IgA nephropathy - Yang, Yang; Li, Xiang; Zou, Honghong; Li, Manna; Wang, Li; Luo, Kaiping; Yan, Wenjun; Li, Yebei; Zhou, Baoqin; Kang, Wenling; Wang, Lijuan; Xu, Shizhang; et al. (Frontiers in Pharmacology, 2025)
BackgroundKunxian (KX) has been reported to be effective in treating Immunoglobulin A nephropathy (IgAN) and autoimmune disorders, such as lupus nephritis, but there is a lack of controlled trial on its effectiveness and safety for treating IgAN.MethodsThis multicenter, prospective cohort study was conducted with individuals aged 18–60 years with biopsy-confirmed primary IgAN, proteinuria greater than 0.75 g/d, and estimated glomerular filtration rate (eGFR) greater than 60 mL/min/1.73 m2. Patients were treated with KX or Mycophenolate mofetil (MMF) after receiving a stable dose of an angiotensin-converting-enzyme inhibitor or angiotensin-receptor blocker for at least 4 weeks.Results67 patients were assigned to the KX group and 72 to the MMF group. The mean (standard deviation) eGFR was 87.75 (15.94) mL/min/1.73 m2, and the mean (standard deviation) proteinuria was 1.70 (0.74) g/d. Patients in the KX group had a greater reduction in proteinuria than those in the MMF group did. Complete remission occurred in 43 patients (64.2%) in the KX group and 37 patients (51.4%) in the MMF group (hazard ratio [HR] 0.612, 95% CI 0.385–0.972, P = 0.038). Overall response occurred in 59 participants (88.1%) in the KX group and 59 participants (81.9%) in MMF group (HR 0.658, 95% CI 0.447–0.970, P = 0.034). Adverse events were observed in 6 patients (8.9%) in the KX group and 5 patients (6.9%) in the MMF group with no significant difference.ConclusionCompared with MMF, KX was safe and significantly decreased proteinuria in IgAN.